Aesthetic lip filler augmentation is not free of adverse reactions: lack of evidence-based practice from a systematic review - Coppini, M.; Caponio, V. C. A.; Mauceri, R.; Pizzo, G.; Mauceri, N.; Lo Muzio, L.; Campisi, G. (Frontiers in Oral Health, 2024)
IntroductionIn the last decades, dermal fillers have gained widespread acceptance for cosmetic purposes since their approval for different health conditions, including lip augmentation and aesthetic intervention of the face. Unfortunately, while filler lip procedures are performed using biomaterials with improved physical characteristics, they are not devoid of adverse drug reactions (ADRs), including those with late-onset.MethodsThis systematic aims to investigate the ADRs associated with lip augmentation procedures using dermal fillers. A systematic review search was conducted in Medline/PubMed, Scopus, Web of Science to answer the PEO question: What are the ADRs in patients undergoing lip augmentation procedures with dermal fillers, and how frequent are they?ResultsThe risk of bias was assessed, and a systematic review was conducted. Nineteen studies were included. In total, 30 patients affected by filler lip ADRs were analyzed, of which 29 were females and only 1 was male with a mean age of 50.9 ± 12.8 years. Hyaluronic acid was the most commonly dermal filler used and granulomatous foreign body reaction was the most common filler lip reaction reported. The mean time between filler lip injection and granulomatous foreign body reaction onset was 57.9 ± 54 months (median 24 months).DiscussionNo study reported ADRs to regulatory authorities. Our results indicate that adverse reactions can occur even long-term after the aesthetic procedure. Therefore, ongoing short-term and long-term follow-up visits are essential, as biocompatible materials are not free from ADRs. Additionally, a lack of reporting ADRs to regulatory authorities has emerged, which is crucial for patient safety.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=534656, identifier: CRD42024534656.